1998
DOI: 10.1016/s0022-5223(98)70273-9
|View full text |Cite
|
Sign up to set email alerts
|

Thymic Carcinoma: Current Staging Does Not Predict Prognosis

Abstract: Patients with thymic carcinoma have a high rate of recurrence. Tumor invasion of the innominate vessels is associated with a particularly poor prognosis. Although Masaoka staging is useful in staging patients with thymoma, it does not appear to predict outcome for patients with thymic carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
104
5
3

Year Published

2002
2002
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(126 citation statements)
references
References 22 publications
14
104
5
3
Order By: Relevance
“…Although there are reports in the literature [8,9] that SCC had a better prognosis than other histologic types of thymic carcinoma, our results did not show this tendency. Contrary to Blumberg and colleagues' [12] report, our data revealed that the prognosis of WD SCC was better than other types of thymic carcinoma. Well-differentiated SCC was defined as low-grade malignancy and was reported as the most reliable predictor of prognosis [4, 6, 9].…”
Section: Commentcontrasting
confidence: 99%
See 2 more Smart Citations
“…Although there are reports in the literature [8,9] that SCC had a better prognosis than other histologic types of thymic carcinoma, our results did not show this tendency. Contrary to Blumberg and colleagues' [12] report, our data revealed that the prognosis of WD SCC was better than other types of thymic carcinoma. Well-differentiated SCC was defined as low-grade malignancy and was reported as the most reliable predictor of prognosis [4, 6, 9].…”
Section: Commentcontrasting
confidence: 99%
“…Herein we reported one of the largest series published thus far. The prevalence of thymic carcinoma compared with all thymic malignant neoplasms was similar to the reports by Hsu and colleagues [11] and Blumberg and colleagues [12]. In Taiwan, the incidence of thymic carcinoma seems higher than in Western countries [8 -11].…”
Section: Commentsupporting
confidence: 84%
See 1 more Smart Citation
“…Therefore, patients with WDTC or type B3 tumors were included in the current study to focus on the prognosis of patients with thymoma, whereas patients with these tumors previously were included in the analysis of patients with thymic carcinomas. 36 The poorer survival and the higher tumor recurrence rate in the patients with type B3 tumors compared with other types of thymomas, however, seem to indicate more careful follow-up and treatment for these patients compared with the treatment for patients with other types of thymomas.…”
Section: Discussionmentioning
confidence: 99%
“…Okumura and associates (37) reported that involvement of the great vessels is an independent prognostic factor in patients with stage III thymoma. 4) The system is not well suited to staging thymic carcinomas (38,39). The TNM system classification of thymic epithelial tumors has not been established.…”
Section: Clinical Stagementioning
confidence: 99%